NFT Become a Copyright Solution - Dw Putu Alit Denbagus Rafli (Catuspata, 2022)
NFT can help art creators to easily register their works for sale using a smart contract system where if the ownership of the work changes hands, the work will become the property of the new owner with proof of a digital certificate. With the steps of making the work so that it can be published in the NFT marketplace media platform and NFT offline gallery. In addition, NFT also has advantages and disadvantages. With that, NFT might be a solution for copyright of a work in the future. However, there are still many questions because NFT is still relatively new and not everyone knows this technology.